A simple experiment to trace stemflow infiltration: Advantages and challenges of using stable isotopes of hydrogen and oxygen and electrical resistivity tomography - G. Zuecco; C. Marchina; M. Censini; D. Todini‐Zicavo; G. Cassiani; M. Borga (Vadose Zone Journal)
Abstract Stemflow is a key process in forested catchments due to its control on soil water content and nutrients’ transport. However, there are still few studies focusing on stemflow infiltration and relying on direct observations that are minimally invasive and repeatable. In this study, we exploited the usefulness of stable isotopes of hydrogen and oxygen, as well as of time‐lapse electrical resistivity tomography (ERT) to investigate water fluxes in the soil. Specifically, we aimed to examine the effectiveness of both isotopes and ERT to trace stemflow infiltration for a beech tree in a steep hillslope in the Italian pre‐Alps, to quantify stemflow infiltration area based on the two methodologies and to provide recommendations for future research. Results showed that both approaches identified an infiltration along the maximum slope gradient with most of the water staying in the upper 45 cm of soil. The analysis of electrical resistivity variations enabled to evaluate the temporal dynamics of stemflow infiltration and to estimate an average stemflow infiltration area of 0.64 m2, which was larger than values found by previous studies based on dye tracers. This high estimate may be due to multiple factors, from the soil conditions to methodological uncertainties. Conversely, the estimation of stemflow infiltration area based on isotopes was affected by the sampling area. Hence, future research based on isotopic tracers needs to consider methods providing a direct field evidence of stemflow infiltration (e.g., dye tracers) or a quick inspection of raw data (e.g., ERT) to inform the sampling design.